ASEAN COMMUNITY 2015 DAN TANTANGANNYA TERHADAP PENDIDIKAN ISLAM DI INDONESIA - Hakim, M. Fathoni (Jurnal Review Politik, 2014)
This paper focuses on the challenges and strategies of Islamic education in Indonesia facing ASEAN Community in 2015. Using qualitative approach the writer finds that Islamic education in Indonesia has encountered a serious number of problems. The majority of Islamic boarding schools (pesantren) are still run in traditional ways (salafi). In addition, the majority of  the school leaders do not posses higher education background. Similarly, higher education level has also dealt with another problematic matter in whichunder graduatestudents are dominant with 93% compare to graduate students with only 7%. These phenomena would be serious problem for Islamic education in Indonesia facing 2015 ASEAN Community. The question is whether Indonesian Muslims are able to compete with other ASEAN member countries, such as Singapore, Malaysia, and Thailand. Another challenge is that the shifting paradigm from the traditional society to the secular-materialistic one. In this context, therefore, the Islamic education in Indonesia is urged to play its pivotal role.